MASTERING READING SKILL FASTER - I GUSTI NGURAH OCTOVA SEVENTILOFA (GANEC SWARA, 2022)
This is a qualitative study in which the author use a literature review paradigm approach. The goal of this research is to discover the quickest technique to increase reading skills. Several periodicals and articles about how to increase one's reading abilities are the focus of this study.The findings of this study reveal that, reading materials and activities should be very interesting for students so that they can easily absorb books, and must be adapted to their level of competence. Teachers should motivate their students to read these materials, be sensitive to their students' comprehension difficulties, and assist their students in changing their attitudes towards reading and developing positive attitudes towards their reading activities so that they can better understand various texts